2019
DOI: 10.1007/s00484-019-01806-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-wave diathermy in the clinical management of musculoskeletal disorders: a pilot observational study

Abstract: Musculoskeletal disorders are the most common cause of pain and functional limitation in the general population. The study aim was to evaluate shortwave diathermy (SWD) effects on pain and quality of life in people with musculoskeletal disorders. Eighty participants (31 men, mean age 56 ± 12.49 years) were enrolled, recruiting from outpatient clinics at the Rehabilitation Unit, University Hospital, Padova. Inclusion criteria were pain lasting more than 15 days, pain visual analog scale (VAS) score higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Although no promising changes in the studied variables were obtained, it has been observed that currently, there are a wide range of standardized protocols for the application of this technique [52]. This means that it is important to highlight the difficulty of establishing the most specific protocol [8]. Although the effect of TT on latent MTPs assessed through the variables analyzed in the present study was small, it is possible that the evaluation of other parameters or the application of other parameters (protocol) could determine the effectiveness of TT on myofascial pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no promising changes in the studied variables were obtained, it has been observed that currently, there are a wide range of standardized protocols for the application of this technique [52]. This means that it is important to highlight the difficulty of establishing the most specific protocol [8]. Although the effect of TT on latent MTPs assessed through the variables analyzed in the present study was small, it is possible that the evaluation of other parameters or the application of other parameters (protocol) could determine the effectiveness of TT on myofascial pain.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, pain reduction is one of the main effects of TT, although more research is needed regarding other physiological aspects. The increase in temperature reduces pain by promoting the vasodilation of tissues affected by pain mediators, such as bradykinin, serotonin, and prostaglandin [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite there being relatively few scientific studies, work at low frequencies (<1 MHz) is used in clinical practice, with the goal of obtaining an increase in tissue temperature as well as other physiological effects. Among the electrophysical factors used in medicine, a wide range of frequencies is used, ranging from 30 kHz to 30 MHz [ 1 , 2 , 3 ]. The factors inducing hyperthermia include the following [ 1 , 4 , 5 ]: Long-wave diathermy—from 3 to 300 kHz (however, this is considered obsolete due to the presence of numerous practical limitations); Short-wave diathermy—from 3 to 30 MHz; Microwaves—from 300 to 3000 MHz (rarely used today).…”
Section: Introductionmentioning
confidence: 99%
“…Among the electrophysical factors used in medicine, a wide range of frequencies is used, ranging from 30 kHz to 30 MHz [ 1 , 2 , 3 ]. The factors inducing hyperthermia include the following [ 1 , 4 , 5 ]: Long-wave diathermy—from 3 to 300 kHz (however, this is considered obsolete due to the presence of numerous practical limitations); Short-wave diathermy—from 3 to 30 MHz; Microwaves—from 300 to 3000 MHz (rarely used today). …”
Section: Introductionmentioning
confidence: 99%